Feasibility of setting up cooperative Adviosory centers for producers،cooperatives in Khorasan-Razavi province - M GHorbani; A Darijani; E Hasanpor; M KHaledi; M Tarshizi (تعاون و کشاورزی, 2009)
It is in view of the undisputed status of consultancy services in policy-making that advisory cooperatives are hypothesized to play a crucial role in generation fine know-how for cooperatives.The current research ،which was conducted in 2006 to verify this،was a field work on 138 cooperative societies in Khorasan-Razavi province to study the feasibility of setthng up advisory cooperative through probing into global experiences to know further about their management structures and workhngs.the societies under study comprised 76 farming and  animal husbandry as well as 62 industrial and mining cooperatives. the results suggested that there are potentials in the province for setting up cooperative advisory centers not only for producers cooperatives، but also for cooperative s of technical ،financial،marketing ،legal،and educational services.as for management structure،involvement of univercity graduates and pundits as advisory centers under the supervision of the Ministry of cooperatives(without jeopardizing their managerial independence) would yield significant efficiency and effectiveness in rendering advisory service to cooperatives.